COLLEGE PROFESSORS' HISTORY: THEIR INITIAL FORMATION CHARACTERISTICS (Fiep Bulletin - online, 2013)
The Physical Education teachers' formation has a complex and recent history in its evolutionary course. The objective of this study was to analyze the professors' history considering their formation course and professional actuation. This is a descriptive research with qualitative emphasis, using the interview technique to support the reflections. The tape recording permitted a deeper analysis of the subjects' considerations and reflections. Ten different professors, formed in different decades (1970's to 2005), performing their occupation at a public university, were interviewed. The interview was based in three questions: their formation's characteristics, competent professional actuation and the actuation diversity facing so much different knowledge. The recreation technique was used to finalize the reflections and analysis. The results showed the diversity in the professors' formation courses were related to each decade. Each decade is characterized by evidencing new actuation axes and the courses evolved in a way to try to fulfill the market demands and the modernity conception of Physical Education. It is possible to affirm that the widest actuation was in the scholar area, with different concepts and applications. It is also possible to cite the sportive initiation and training, the leisure, the gyms, the care of people with special needs, etc. The professionals' speeches show that only the initial formation courses, facing the many exigencies, won't be able to promote the abilities, competences and tools for the great performance as a professional. Therefore, we are at a crossroad: on this side the market, on the other side the professional performance. The men, as future professionals, are showing their outlines, so their formation and actuation are appropriate according to the humanity principles. We should be alert and act to promote the salutary changes.
Keywords: teachers' formation; physical education; professional actuation